أثر الدلالات البلاغيّة في فهم النص القرآني: دراسة تطبيقية لآيات مختارة = The effect of rhetorical indications on understanding the Qurʾan text an applied study of selected verses = Kesan panduan retorik dalam memahami teks Al-Quran kajian terapan terhadap ayat-ayat terpilih - Hussein, Nasr El Din Ibrahim Ahmed (IIUM Press, International Islamic University Malaysia, 2020)
يعتبر- هذا البحث – أثر الدلالات البلاغيّة في فهم النص القرآني: دراسة تطبيقية لآيات مختارة- حيث ركّزت الدراسة خاصة على التراكيب والتعابير التي تمسّ الفنون البلاغيّة، للوقوف على الدلالات الخفية والمعاني واللطائف التي تحملها بين طيّاتها. وتتجلى أهميته من خلال فتح أعين المتدبرين في نصوص التنزيل وتوجيهها إلى عظمة هذا الحقل الدلالي الواسع المتمثل في البيان القرآني. ثم بيان لطائف الأثواب البيانيّة التي تكمن في النص القرآني المعجز. وبيان الفروق الجمالية الدقيقة التي ما كان لقارئ القرآن أن يتذوقها لولا ورودها في ذلك الثوب البياني الأخّاذ. وهو بذلك يجلي السبق القرآني في كيفية استعمال تقنيات التعبير وتوظيفها في الخطاب البلاغي واللغوي والأدبي.كما يوضح ما تميّز به القرآن الكريم من أساليب بلاغية متنوعة، وتصاوير رائعة فاقت طوق البشر. وبالطبع لا يمكن فهم النص القرآني دون معرفة تلك الدلالات والإشارات التي تكشف ما وراء النص القرآني، أو الخطاب القرآني من معاني خفيّة، يصعب على الدارس فهمها دون استخدام هذه الوسائل البلاغيّة، وتحليلها تحليلاً علميّاً يؤدي إلى كشف تلك الدلالات.ومشكلة البحث تتعلق بكيفية فهم تلك الإشارات البلاغيّة، والدلالات الخفيّة التي تحيط بالأسلوب القرآني. وهي عمل شاق يحتاج إلى بصيرة وبصر، كما يحتاج إلى تعمّق وتفكير وتأمل. فالمسألة شائكة، والعمل فيها يحتاج إلى صبر وإلمام عميق بعلوم اللغة؛ من نحو وصرف، وعلوم البلاغة؛ من بيان، وبديع، ومعاني. وتدور أسئلة البحث حول: كيف يتعامل الدارس مع النص القرآني؟ وكيف يمكن استنباط المعاني الخفيّة من النص القرآني؟ وما قيمة فهم الإشارات التي تردّ في القرآن الكريم؟ كيف نتعمّق ونستوعب أسلوب القرآن الكريم؟ وما الوسائل التي تعين المجتمع في فهم القرآن الكريم فهماً عصريّاً معتدلاً؟ وما الطرق إلى تحليل الدلالات البلاغيّة في النص القرآن الكريم؟ وأهداف البحث أنه يخدم المسلم وغير المسلم في فهم الخطاب القرآني. ويساعد طلبة العلم – على اختلاف تخصصاتهم- في كيفية التعامل مع النص القرآني. كما يساعد في استباط المعاني الخفيّة من النص القرآني؛ شارحاً ومحللاً. ويشرح ويوضّح الأشارات التي ترد في القرآن الكريم. ومنهجيّة البحث، تشير إلى – المنهج الاستقرائيّ، والمنهج التحليلي؛ الذي يقوم بتقديم بعض النماذج المختارة من الآيات واستيعابها بعمق، ثم تحليلها، ومناقشتها، واستنباط الدلالات البلاغيّة الخفيّة. ونسأل الله تعالى التوفيق. **************************************************************************** The research focuses on the study of rhetorical indication and its impact on the understanding of the qurʾanic text. And focused particularly on the structures and expressions that affect the rhetorical arts, to stand on the connotations and meanings and subtleties borne fraught. And its importance is reflected through the eyes open almtdberian in the texts of the download and routed to the greatness of this semantic field is wide of the qur'anic statement. Then for some professional graphic statement dresses which lies in the qur'anic text miraculous. The statement minute aesthetic differences that would not have tasted that the qurʾan reader not to their appearance in this chart is breathtaking dress. It thus explains lead in how to use the Qur'anic expression and techniques employed in the Rhetoric and linguistic Literary discourses. And illustrates what characterized the Qurʾan from a variety of Rhetorical styles, exquisite representations of superhuman collar. And, of course, can not understand the text of the Quran without knowing those signs and signals that reveal what behind the Quranic text, or Qur'anic discourse of hidden meanings, it is difficult for the student to understand without the use of these Rhetorical means, and analyzed scientifically analysis leads to the detection of those Aldalalat. The Research's Problem: How such understanding Rhetorical signals, and hidden connotations that surround the Qur'anic style. It is hard work needs to insight and vision, and needs to be deepened and reflection and meditation. A thorny issue, and where the work requires patience and a deep knowledge of the science of language; some of the exchange, and the science of rhetoric; the statement, and adorable, and meanings. The research questions revolve around: how to deal with student Qur'anic text? How can devise hidden meanings of the Qur'anic text? And the value of understanding the signals that are contained in the Koran? How to go deeper and understand the Koran style? And the means by which the community had to understand the Qur'an understanding fashionably moderate? The road to the semantic analysis of the Rhetorical text in the Qur'an? The Objectives of the Research that serves the Muslim and non-Muslim to understand the Qur'anic discourse. And helps students - the difference specializations and field of studies- in how to deal with the Qur'anic text. It also helps to explain the hidden meanings of the Qur'anic text; explaining and analysts. He explains and illustrates the signals that are contained in the Qur'an. And Research Methodology, refers to - the inductive method, and analytical approach; who withholds count of selected models of the verses and deeply absorbed, then analyzed, and discussed, and devise signals Rhetorical ones. ****************************************************************************** Kajian ini adalah mengenai penyelidikan terhadap panduan retorik dan kesannya dalam memahami teks Al-Quran. Ia tertumpu terutamanya pada struktur dan ekspresi yang mempengaruhi kesenian retorik, untuk mengetahui konotasi (maksud tersirat), makna dan kehalusannya. Kajian ini mampu membuka mata para pentafsir teks-teks al-Quran untuk memahami keluasan kenyataan al-Quran seterusnya menjelaskan penggunaan kenyataan grafik professional yang terdapat dalam teks al-Quran yang bermukjizat. Penjelasan terhadap perbezaan estetika yang tidak akan dirasakan oleh pembaca Al-Quran tanpa panduan reotrik adlah sesuatu yang menarik. Oleh itu, jelas menerangkan bagaimana penggunaan ekspresi dan teknik-teknik Al-quranyang digunakan dalam panduan retorik dan gaya bahasa serta. Ia menggambarkan keunikan Al-Qur'an yang mempunyai pelbagai gaya retorik yang diluar kemampuan manusia. Tanpa petunjuk yang mendedahkan maksud tersirat teks, sudah tentu teks al-Quran tidak dapatdifahami dengan baik. Masalah Penyelidikan: Bagaimana cara untuk memahami panduan retorik, dan konotasi tersembunyi yang terdapat dalam al-Quran. Ia merupakan satu usaha jitu yang memerlukan pemfokusan yang mendalam, pemikiran yang tajam dan penelitian. Yang paling utama, ia memerlukan kesabaran yang tinggi dan pengetahuan yang luas dalam sains bahasa seperti: ilmu nahu (ilmu berkenaan harkat (baris) sesuatu kalimat) dan sorof (perubahan bentuk kata), ilmu balaghah (retorik), ilmu bayan (gaya Bahasa penyampaian), ilmu badi’ (ilmu memperindahkan Bahasa), dan ilmu maa’ni (ilmu berkenaan hal ehwal bahsa arab mengikut kondisi). Soalan kajian: bagaimanakah seseorang dapat memahami teks Al-Quran? Bagaimanakah seseorang dapat merungkai makna tersirat teks Al-Qur'an? Apakah kelebihan atau nilai memahami panduan atau petunjuk yang terkandung dalam Al-Quran? Bagaimana hendak pergi lebih mendalam dan memahami gaya bahasa Al-Quran? bagaimanakah cara masyarakat harus ikuti untuk memahami Al-Qur'an dengan mudah? Dan apakah cara untuk menganalisa teks retorik dalam Al-Qur'an? Objektif kajian: Dapat membantu orang Islam dan bukan Islam dalam memahami teks al-Quran, seterusnya membantu para pelajar dari pelbagai bidang dan pengkhususan pengkhususan dalam memahami ayat-ayat Al-Qur'an. Ia juga membantu menjelaskan dan menganalisa makna tersembunyi teks Al-Qur'an serta menerangkan panduan yang terkandung dalam Al-Qur'an. Kaedah Penyelidikan: merujuk kepada kaedah induktif, pendekatan analisa dengan mengambil contoh ayat-ayat terpilih.